Heuristics based on simulated annealing applied to the issue of berth allocation - Mauri, Geraldo Regis; Oliveira, Alexandre César Muniz de; Lorena, Luiz Antonio Nogueira (Revista Gestão da Produção Operações e Sistemas, 2008)
This work presents a Simulated Annealing based heuristic to solve the Berth Allocation Problem. This problem approaches the programming and allocation of ships to mooring areas along a quay. The problem is modeled as a Multi-Depot Vehicle Routing Problem with Time Windows. The Simulated Annealing application uses three types of neighbors moves that are randomly selected. The computational results are obtained through tests problems used in a recent work and compared against CPLEX and other method found in literature. Keywords: Berth Allocation Problem; Simulated Annealing; Vehicle Routing.